Kína bankrendszerének fejlődése és reformjai, jelenlegi helyzete - Pencz, Helga; Szalai, Gergely (Közép-Európai Közlemények, 2017)
China as a world-power is actually possessing one of the largest economy and geopolitical status in the world. The foreign trade of China has been increased rapidly thanks to mainly the accession to the WTO, in 2010 within one year it expanded with 37% and obviously the banking system of the country also has to meet these requirements. The executed research work is analyzing the aspect of this question mark, how could the Chinese banking system correspond to the new challenges and what kind of reforms did it go through in the past decades. Several research works have been revealed from Chinese economists who are introducing in detail the banking system of the country, their datas and also their effects to the economy. Nevertheless another topic is also coming up for discussion, which foreign banks could effect the banking system of the country with what kind of effects and how the foreign investors can dispose of advantages and disadvantages. Furthermore the study pans out about the datas of the economical and banking system of China, the followed challenges, problems and successes.